Proposing a working definition and framework to evaluate Islamic websites - Mahmud, Murni; Aliyu, Mansur; Hussien, Idyamawati; Md. Tap, Abu Osman (2011)
This paper proposes a working definition and framework to evaluate content and design of Islamic Website. There are two studies described in this paper. Firstly, a single user study was conducted to examine fifty (N=50) Islamic websites in order to analyse the working definition of Islamic Website. Secondly, seventy-eight (N=78) Muslim Internet users were investigated on their perceptions of Islamic Website definition. The study revealed that Islamic Website is determined by the characteristics and quality of the content. Quality of Islamic Website is grouped into two categories: design and content. Design features consist of navigation, interactivity and attractiveness; content features consist of legitimacy, objectivity, authority, relevance, credibility and reliability. The main contributions of this paper are the working definition of Islamic Websites and a framework to evaluate religion-based websites, particularly Islamic websites.